PENGARUH NET WORKING CAPITAL DAN OPERATING CASH FLOW TERHADAP CASH HOLDING PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fatmawati, Ade Pipit; sarifah, sarifah (Universitas Logistik dan Bisnis Internasional, 2025)
In conducting business activities, there must be a significant change in the situation to affect business activities. The COVID-19 pandemic that has hit the world since the beginning of 2020 has had a significant impact on a variety of sectors, including the property and real estate sectors. This leads to a decrease in revenue and profits, which also results in a fall in corporate cash, which can cause companies to struggle to meet their short-term obligations and lose investment opportunities. Companies need to anticipate this by estimating the optimum amount of cash holding to balance the company's operational fund needs. The aim of this study is to look at the influence of Net Working Capital and Operating Cash Flow on Cash Holding. This study uses quantitative research methods and sample techniques using purposive sampling. Data processing using the SPSS version 27 application with the analytical tools used are normality tests, product moment correlation tests, double correlation tests, duplicate regression tests, determination coefficients, F tests, and T tests. The results of the tests in this study showed that partially net working capital has no influence on cash holdings, while operating cash flow partially has influence over cash holdings. Meanwhile, simultaneously, net working capital and operating cash flow have a significant influence on cash holdings.